EFL Teachers’ Perceptions on the Use of L1 in EFL Classroom: A Case Study of Junior High School Level - Desi Purnama S.W; I Putu - Sukmaantara; Bambang Arya Wija P (Institut Agama Islam Negeri Palopo, 2022)
Since its independence, the Indonesian government has recognized English as one of the most important international languages for communication. As a result, the government has suggested that English become a mandatory subject in Junior High School. According to Nurkamto (2003), English is taught and utilized as a foreign language in Indonesia (FL). Bahasa Indonesia is our native or first language (L1). As a result, the teachers' perceptions of using L1 in the classroom are more appealing to discuss. The qualitative case study approach was employed in this study to evaluate teachers' perceptions about the use of LI in the EFL classroom. The researcher employed interviews to collect data for this study. The interview was conducted once in order to obtain information on the teachers' perceptions about the use of L1 in the EFL classroom. Because they had been teaching for several years, the researcher selected three English teachers from SMP NEGERI 3 Muncar to participate in this study. They also have a lot of experience attending workshops and seminars to further their professional growth. In assessing the data, the researcher used Creswell's (2012) model